Under the wide and starry sky : a novel - Horan, Nancy (Ballantine Books Trade Paperbacks, 2014)
"In her masterful new novel, Nancy Horan has recreated a love story that is as unique, passionate, and overwhelmingly powerful as the one between Frank Lloyd Wright and Mamah Cheney depicted so memorably in Loving Frank. Under the Wide and Starry Sky chronicles the unconventional love affair of Scottish literary giant Robert Louis Stevenson, author of classics including Treasure Island and The Strange Case of Dr. Jekyll and Mr. Hyde, and American divorcee Fanny Van de Grift Osbourne. They meet in rural France in 1875, when Fanny, having run away from her philandering husband back in California, takes refuge there with her children. Stevenson too is escaping from his life, running from family pressure to become a lawyer. And so begins a turbulent love affair that will last two decades and span the world"--